(untitled) (مجلة دراسات إقلیمیة, 2026)
Research Idea: It examines Turkey’s military presence in the Middle East and the transformation of Turkish security doctrine from the policy of "Zero Problems" and reliance on soft power to the adoption of a "Forward Defense" doctrine. It explores the shift from participation in collective international missions to an independent military presence following the geopolitical changes that emerged after 2011. Objective: The research aims to map the distribution of Turkish military bases across the Middle East, analyze the strategic motivations behind their establishment, and assess their impact on the regional balance of power and on host states. Methodology: The research employs a descriptive-analytical approach to examine the evolution of Turkish security doctrine and the implications of Turkey’s military presence. The analysis draws on official statements issued by the Turkish Ministry of Foreign Affairs and relevant strategic reports. Results: The findings indicate that the militarization of Turkish foreign policy has enabled Turkey to balance regional powers, particularly Iran and Russia, and strengthen its national security along its borders with Syria and Iraq. However, this policy has also generated political costs and contributed to regional isolation. Moreover, Turkey’s military presence has evolved beyond immediate security concerns to serve broader strategic objectives, including securing maritime influence and safeguarding energy supplies. Conclusion: The research concludes that, despite the geopolitical gains achieved through the militarization of Turkish foreign policy, this strategy has confronted Turkey with the challenges of high economic costs and regional isolation. The findings also underscore the need for coordinated Arab action to address the implications of Turkey’s military presence for the sovereignty of host states.